An outlook on the role of decaffeinated coffee in neurodegenerative diseases. Issue 5 (8th March 2020) - Colombo, Raffaella; Papetti, Adele
Abstract: Coffee is reported to be among the most widely consumed beverages in the world and coffee consumption has been associated with reductions in the risk of several chronic diseases. Among its constituents, caffeine represents the most investigated component. The main impact of caffeine on health is associated with the central nervous system, the cardiovascular system, the inflammatory mechanisms, the metabolism of carbohydrates, and the cancer. Current research is devoted to the role of this compound and its analogs or derivatives on neuroinflammation and neurodegenerative disorders, mainly Alzheimer's Disease and Parkinson's Disease. However, coffee is also rich in polyphenols, mainly phenolic acids (chlorogenic acids, caffeic acid, ferulic acid), quinic acid, and quercetin. Many aspects still require greater clarification, including the effect of coffee compounds different from caffeine, on several pathologies. This review aimed to provide a comprehensive overview of the potential benefits of decaffeinated coffee constituents, focusing the attention on neurological processes and pathologies, such as mainly memories disorders, Parkinson's Disease, neurophatic pain disorders, and cerebral ischemia.